2009
DOI: 10.1159/000268105
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Fentanyl Analgesia by Antidepressants

Abstract: Clinical practice often requires simultaneous administration of antidepressants with opioids (oncology, rheumatology). Coadministration may either attenuate or potentiate opioid analgesia. The purpose of this paper was to verify how the analgesic action of fentanyl (0.05 mg/kg) is affected by single administration as well as 4- or 21-day premedication with antidepressants characterized by various mechanisms of action. The effects of amitriptyline 3 mg/kg, moclobemide 5 mg/kg, fluoxetine 5 mg/kg and reboxetine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Our previous observations and the works by other authors showed that potential changes in co-analgesic action should be visible within 3 weeks of administration. Type of repeated treatment used in this study resembles the co-analgetic use of antidepressants in clinical practice and the same model of drug administration was used in previous publications [15][16][17].…”
Section: Time Schedulementioning
confidence: 99%
See 2 more Smart Citations
“…Our previous observations and the works by other authors showed that potential changes in co-analgesic action should be visible within 3 weeks of administration. Type of repeated treatment used in this study resembles the co-analgetic use of antidepressants in clinical practice and the same model of drug administration was used in previous publications [15][16][17].…”
Section: Time Schedulementioning
confidence: 99%
“…The nociceptive thresholds in this part were determined on day 19 (acute VFX) or on day 39 (repeated VFX) of study, 30 min before VFX/MRF administration (baseline value) and at 30, 60, 90, 120, 150 and 180 min after morphine-venlafaxine injection. Timing of thresholds measurements was taken from earlier an work by Juś et al [17]. For controls, baseline thresholds values were determined 30 min before administration of (controls 1 and 3) 0.9% NaCl with 0.5% MC and (control 2) MRF in 0.9% NaCl + 0.5% MC; next measurements were conducted at the abovementioned time points.…”
Section: Time Schedulementioning
confidence: 99%
See 1 more Smart Citation
“…Garrett, 2011 68 Study drug is a combination of amitriptyline, ketoprofen, and oxymetazolin. Juś, 2010 69 Animal study. Krimmer, 1986 70 Not an RCT.…”
Section: Competing Interestsmentioning
confidence: 99%